Ramping Up Antimicrobial Peptides Against Severe Acute Respiratory Syndrome Coronavirus-2 - Ghosh, Santosh K.; Weinberg, Aaron (Frontiers in Molecular Biosciences, 2021)
Human-derived antimicrobial peptides (AMPs), such as defensins and the cathelicidin LL-37, are members of the innate immune system and play a crucial role in early pulmonary defense against viruses. These AMPs achieve viral inhibition through a variety of mechanisms including, but not limited to, direct binding to virions, binding to and modulating host cell-surface receptors, blocking viral replication and aggregation of viral particles, and indirectly by functioning as chemokines to enhance or curb adaptive immune responses. Given the fact that we are in a pandemic of unprecedented severity, and the urgent need for therapeutic options to combat severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), naturally expressed AMPs and their derivatives have the potential to combat coronavirus disease 2019 (COVID-19) and impede viral infectivity in various ways. The fact that development of effective treatments is an urgent public health priority, AMPs and their derivatives are being explored as potential prophylactic and therapeutic candidates. Additionally, cell-based platforms, such as human mesenchymal stem cell (hMSC) therapy, are showing success in saving the lives of severely ill patients infected with SARS-CoV-2. This could be partially due to AMPs released from hMSCs that also act as immunological rheostats to modulate the host inflammatory response. This review highlights the utilization of AMPs in strategies that could be implemented as novel therapeutics, either alone or in combination with other platforms, to treat CoV-2-infected individuals.